Terminology on abandonment of domestic animals for use in Latin America (Research, Society and Development, 2022)
Pet abandonment is a worldwide social problem that affects humans, animals, and the environment, being, therefore, a One Health problem. Global research seeks to understand the causes of pet abandonment in order to implement effective interventions. However, the various terms used cause problems in understanding. The standardization of animal abandonment terms is necessary and can help research on the topic. The purposes of this study were to search, through a narrative review, the most used definitions to denominate the action of a caretaker in giving up the guardianship of a pet, highlighting the difference between the terms, and, finally, to propose terms for the Latin American reality. The terms suggested for use in Latin America are “owner surrender”, “adoption”, “transfer”, “abandonment”, “trap”, and “return”.